Influence of Customer Relationship Strategy and Product Innovation on Marketing Performance of Small and Medium Enterprises (SMEs) in Bekasi City Indonesia - Winarso, Widi; Limakrisna, Nandan; Muharam, Hari (Dinasti Publisher, 2025)
This study is to determine the influence of customer relations and Innovation Product to Performance Marketing Small and medium enterprises UKM in Bekasi City. This research is a quantitative research. The object of this research is UKM actors in field food in Bekasi City. Technique collection data Which used in study This is with use questionnaire. Study This done with technique incidental sampling with amount sample that is 100 respondents. Analysis Which used in study This is analysis descriptive with model regression linear let's go. The results showed that (1) partial use of Customer Relations has a positive and significant effect on the performance business of SMEs, (2) partial innovation has a positive and significant effect on the performance of SMEs, (3) simultaneously the use of Customer Relations and innovation has a positive and significant effect on the marketing performance of SMEs.